Water sorption isotherm of Aceh Rice (Oryza sativa): Study on chemical properties and characteristics - Hayati, R.; Synthia, D.; Marliah, A.; Munawar, A. A. (International Journal of Agricultural Technology, 2021)
The chemical properties and isothermic characteristics of water absorption in Aceh rice was investigated. The results showed that Aceh Mutan M4 local rice had 3 bound water fractions, namely 7.1% db, 12.3% db and 169.5% db. Type of water bound to the area of Primary Bonded Water (PBW), Secondary Bonded Water (SBW), and Tertiery Bonded Water (TBW) of Aceh local rice were Mp = 7.1% db, Ms = 12.3 % db, and Mt = 169.5% db. Storage of rice for 15 days in the ATP area of product quality did not damage or change, storage in ATS became older in color, while storage in ATT areas decreased product quality which was indicated by the presence of fungus. The implication of this research suggested that local Aceh rice should be stored at a water content of <7.1%, because the first critical points of Aceh local rice was Mp 7.1% db and equilibrium ap = 0.53